Hurdle Technology: Principles and Recent Applications in Foods - Nura Abdullahi; Munir Abba Dandago (Indonesian Food and Nutrition Progress, 2020)
The application of hurdle technology in food preservation is progressing. The technology is becoming more acceptable among researchers in the field of food preservation due to its effectiveness at mild levels. The effects of conventional preservation techniques are minimized by hurdle technology through a smart combination of preservatives at less severe levels. Considerable advancement in the application of hurdle technology is realized in both developed and developing nations. Nutritional and sensory qualities were protected through the smart use of combined preservation. The safety and stability of foods were ensured using this technology, and many perishable foods are now ambient stable. This article reviewed the principles of hurdle technology and reported the recent applications of the technology in the preservation of foods from plant and animal origins.